V27. Distribution of epileptogenicity in focal cortical dysplasias assessed with combined grid and depth electrode sampling. Issue 8 (August 2015) - Gollwitzer, S.; Valente, I.; Rodionov, R.; Ritter, L. Mantoan; Wehner, T.; Hamer, H.; Bartolomei, F.; Diehl, B.
<x xml:space="preserve">Abstract</x> Objectives In focal cortical dysplasia (FCD) lesion boundaries are difficult to delineate on MRI and scalp EEG can be poorly localizing. Therefore, intracranial EEG (iEEG) is often necessary to define the extent of the epileptogenic lesion. While subdural grid electrodes provide high spatial resolution and enable excellent mapping of cortical function, depth electrodes allow for intra-lesional and deep cortical sampling. It was the aim of this study to evaluate the contribution of both modalities in a combined iEEG approach and to assess the utility of a novel semi-automated tool for iEEG analysis, the Epileptogenicity Index (EI) (Bartolomei et al., 2008). Methods 15 patients with intractable epilepsy due to FCD underwent invasive EEG with a combination of subdural grid and depth electrodes. Three habitual seizures were reviewed visually to determine ictal EEG onset. Additionally we computed the EI that takes into account the propensity of brain tissue to generate rapid discharges and the delay until a given structure is involved in the seizure after onset. Thus, a quantifying index ranging from 0 to 1 is generated for each electrode separately. Results 1. Visual analysis. The ictal onset zone was located deep, sampled by the depth electrodes in 6 cases, seizures originated from the gyral surface, sampled by grid or the most lateral depth electrode contacts in 9 patients. Seizures with surface onset first involved electrodes overlying the lesion in 6 cases and electrodes remote from it in 3 cases. Seizures originating from the depth affected only intra-lesional contacts in 3, both intra- and extra-lesional electrodes in 2 and exclusively normal appearing tissue in 1 patient. 2. EI analysis. Compared to visual analysis, EI depicted the time of ictal EEG onset accurately in 13 out of 15 cases. EI localisation of ictal onset was concordant in 6 cases, moderate agreement was reached in 2 cases, while in 7 patients EI failed to capture involved electrodes correctly. Main prerequisite for good applicability of the EI was an ictal pattern consisting of fast activity in the beta and gamma range. High frequency oscillations >70 Hz and rhythmic spikes were largely missed. 3. Impact on surgical decision. Using ictal EEG information from the grids, the epileptogenic zone differed from the MRI lesion in 9 patients; depth electrodes revealed such results in 3 additional cases. Accordingly, proposed resection exceeded imaging pathology in 8 patients while in 4 cases functional cortex overlying the lesion was spared. No surgery was performed in 4 patients due to an overlap between epileptogenic and eloquent cortex. An ILAE class 1 outcome was achieved in 9 patients (82%). Discussion Although intrinsic epileptogenicity is generally assumed in FCD, seizures can also be generated within gyral or deep tissue appearing normal on imaging. In consequence, investigating FDC with a combination of subdural grid and depth electrodes is the most efficient approach to outline the three dimensional epileptogenic lesion. The EI is a helpful additional tool to measure the epileptogenicity and support visual analysis. It is applicable for grid and depth electrodes. However, a specific ictal pattern is prerogative for reliable results.